2014
DOI: 10.1292/jvms.13-0248
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Testicular Ischemia-Reperfusion Injury in Rats

Abstract: Testicular torsion is a urological emergency that leads to serious testicular damage and male infertility. We performed this study to identify specific proteins that are differentially expressed in response to testicular torsion and detorsion-induced ischemia-reperfusion (I-R) injury. Adult male rats were divided into two groups: a sham-operated group and a testicular I-R group. Testicular torsion was induced by rotating the left testis 720° in a clockwise direction for 1 hr, and then, detorsion was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…An Olympus light microscope (Olympus, Japan) was used for capturing pictures and ImageJ was used for the analysis of pictures. A total of five images were captured and analyzed per group while focusing specifically on neuronal cells morphological integrity, such as size, shape, infiltrated cells, and vacuolation (Ouh et al, 2014).…”
Section: Hematoxylin Eosin (Hande) Stainingmentioning
confidence: 99%
“…An Olympus light microscope (Olympus, Japan) was used for capturing pictures and ImageJ was used for the analysis of pictures. A total of five images were captured and analyzed per group while focusing specifically on neuronal cells morphological integrity, such as size, shape, infiltrated cells, and vacuolation (Ouh et al, 2014).…”
Section: Hematoxylin Eosin (Hande) Stainingmentioning
confidence: 99%
“…The author did not provide further information on what NK cell markers they have investigated. ( ii ) In the testicular torsion, proteomic study of rat testis indicated the upregulation of killer cell lectin-like receptor 16 which can be an NK cell activating receptor 17 . ( iii ) Increase of CD56+ NK cells in the semen of a subgroup of subfertile men 18 .…”
Section: Hypothesismentioning
confidence: 99%
“…( ii ) In the testicular torsion, proteomic study of rat testis indicated the upregulation of killer cell lectin-like receptor 16 which can be an NK cell activating receptor 17 .…”
Section: Hypothesismentioning
confidence: 99%